EVALUATION OF THE QUALITY OF LICENSING SERVICES AT THE INVESTMENT SERVICES AND ONE DOOR INTEGRATED LICENSING SERVICES IN NORTH SUMATRA PROVINCE - Ariani Rambe, Sangkot; Asmara, Sakhyan; Ridho, Hatta (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
Licensing services at the Investment Service and One-Stop Integrated Licensing Services of North Sumatra Province are still experiencing problems and problems related to Information and Technology systems, the absence of Regional Regulations regarding guidelines for licensing or regulations, facilities and infrastructure that are less supportive and the number of public complaints regarding licensing services which can be seen through television and internet media. This study aims to determine the quality of licensing services at the Office of Investment and One-Stop Integrated Licensing Services in North Sumatra Province. This research is descriptive research with a qualitative approach. Data collection techniques using the method of observation, interviews and documentation. The theory used is SERVQUAL Theory by Zeithaml, Parasuraman and Berry mention five dimensions in determining service quality, namely Tangibles (physical evidence), Reliability (reliability), Responsiveness (responsiveness), Assurance (guarantee) and Empathy (empathy). The results showed that the quality of service at the Investment Service and One-Stop Integrated Licensing Services of North Sumatra Province for the Tangibles and Assurance dimensions did not match what the community expected, while the service quality for the Reliability, Responsiveness and Empathy dimensions were in accordance with what the community expected.